2016
DOI: 10.1371/journal.pone.0160124
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal Metagenomic Analysis of Hospital Air Identifies Clinically Relevant Microbes

Abstract: We describe the sampling of sixty-three uncultured hospital air samples collected over a six-month period and analysis using shotgun metagenomic sequencing. Our primary goals were to determine the longitudinal metagenomic variability of this environment, identify and characterize genomes of potential pathogens and determine whether they are atypical to the hospital airborne metagenome. Air samples were collected from eight locations which included patient wards, the main lobby and outside. The resulting DNA li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…The attached Supporting Information file provides additional information about the version of ZovaSeq used for King et al 2016 [1], which is currently available for use from Zova Systems (contact robert.yamamoto@zovasystems.com; also see https://lnkd.in/gxkRCVV). ZovaSeq has since been updated and further optimized.…”
mentioning
confidence: 99%
“…The attached Supporting Information file provides additional information about the version of ZovaSeq used for King et al 2016 [1], which is currently available for use from Zova Systems (contact robert.yamamoto@zovasystems.com; also see https://lnkd.in/gxkRCVV). ZovaSeq has since been updated and further optimized.…”
mentioning
confidence: 99%
“…Metagenomics has emerged as a new molecular method to characterize diverse bioaerosols, which first quantified and identified bioaerosols in agriculture and has most recently been used for healthcare aerosols (King et al, 2016;Nonnenmann et al, 2010;O'Brien et al, 2016). Within the healthcare setting, several of the microorganisms cultured from previous studies were identified to exist as well as other microorganisms that have not yet been cultured (King et al, 2016). Results suggest healthcare settings may consist of more microorganism species than originally hypothesized (King et al, 2016) Challenges of Sampling Bioaerosols in a Healthcare Setting…”
Section: Analysis Methods For Collected Bioaerosolsmentioning
confidence: 99%
“…Molecular based analysis occurs when bioaerosols are collected or extracted into liquid solution where the DNA or RNA are analyzed, however viability of the microorganism may not be determined (ACGIH, 1999). Molecular analysis can include techniques such as polymerase chain reaction (PCR) or metagenomic techniques (e.g., shotgun sequencing) (King et al, 2016;Mukoda, Todd, & Sobsey, 1994;Nonnenmann, Bextine, Dowd, Gilmore, & Levin, 2010;O'Brien et al, 2016;Stetzenbach, Buttner, & Cruz, 2004). PCR is the oldest molecular method that quantifies microorganisms obtained in a sample and is limited for use in microorganisms which have a fully or partially sequenced genome (Mukoda et al, 1994).…”
Section: Analysis Methods For Collected Bioaerosolsmentioning
confidence: 99%
See 2 more Smart Citations